2007
DOI: 10.1039/b616443a
|View full text |Cite
|
Sign up to set email alerts
|

The growth of ErxGa2−xO3films by atomic layer deposition from two different precursor systems

Abstract: The atomic layer deposition (ALD) growth of Er x Ga 22x O 3 (0 ¡ x ¡ 2) thin films was demonstrated using two precursor systems: Er(thd) 3 , Ga(acac) 3 , and ozone and Er(C 5 H 4 Me) 3 , Ga 2 (NMe 2 ) 6 , and water at substrate temperatures of 350 and 250 uC, respectively. Both processes provided uniform films and exhibited surface-limited ALD growth. The value of x in Er x Ga 22x O 3 was easily varied by selecting a pulse sequence with an appropriate erbium to gallium precursor ratio. The Er(thd) 3 , Ga(acac)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…First, the bulk phase diagram can be used to ascertain which cycle ratio (to tune the composition) and annealing conditions (to tune mixing and phase) need to be employed. In most cases, ALD of a film with the correct stoichiometry does not directly result in a crystalline phase, and a post-deposition anneal is required (this can also be seen in Tables –). ,,,, ,,,, ,,, ,,,,,,,,,,,,,, Typical annealing conditions are under nitrogen or oxygen atmosphere or in air, and the temperature required to begin crystallization is generally between 600 and 800 °C, with the required temperature often varying depending on the composition of the film. However, while the phase diagram provides thermodynamic information on the bulk system, it has been shown that it often does not rigorously predict the formation of phases in ALD films. , This phenomenon has been hypothesized to be a result of the layer-by-layer growth character of ALD or of bulk material data not applying to the nanometer thickness scale of ALD films, but further investigation is required to unravel the effects.…”
Section: Intermixing and Phase Formationmentioning
confidence: 99%
“…First, the bulk phase diagram can be used to ascertain which cycle ratio (to tune the composition) and annealing conditions (to tune mixing and phase) need to be employed. In most cases, ALD of a film with the correct stoichiometry does not directly result in a crystalline phase, and a post-deposition anneal is required (this can also be seen in Tables –). ,,,, ,,,, ,,, ,,,,,,,,,,,,,, Typical annealing conditions are under nitrogen or oxygen atmosphere or in air, and the temperature required to begin crystallization is generally between 600 and 800 °C, with the required temperature often varying depending on the composition of the film. However, while the phase diagram provides thermodynamic information on the bulk system, it has been shown that it often does not rigorously predict the formation of phases in ALD films. , This phenomenon has been hypothesized to be a result of the layer-by-layer growth character of ALD or of bulk material data not applying to the nanometer thickness scale of ALD films, but further investigation is required to unravel the effects.…”
Section: Intermixing and Phase Formationmentioning
confidence: 99%
“…However, to be used in CVD or ALD one of the most important attributes is the availability of a volatile precursor of metal. Ga 2 O 3 thin film formation has been previously studied using Ga(acac) 3 , , ((CH 3 ) 2 GaNH 2 ) 3 , and Ga(N(CH 3 ) 2 ) 6 . , However, all of these precursors have to be heated to achieve an efficient vapor pressure. Trimethylgallium (TMGa) , is an important organometallic precursor for Ga 2 O 3 thin films due to its high vapor pressure at room temperature .…”
Section: Introductionmentioning
confidence: 99%
“…The carbon contamination in CaS:EuO could be explained by the reaction between ozone and the β-diketonate precursor (Eu(thd) 3 ), which is known to originate carbonates in the films [14]. Additionally, the ToF-ERDA analysis revealed a lower hydrogen presence in CaS:Eu, which indicates the excellent reactivity between Ca(thd) 2 and Eu(thd) 3 with H 2 S. These efficient surface reactions are responsible to effectively remove lighter species, such as H [36]. In contrast, higher levels of carbon and hydrogen contamination in CaS:EuO sample can be correlated with the lower reactivity of O 3 species with Ca(thd) 2 and Eu(thd) 3 , in comparison to H 2 S. Moreover, the intentional inclusion of oxygen atoms into the europium doped CaS layer may be the major responsible factor for the lower level of crystallinity.…”
Section: Discussionmentioning
confidence: 99%